ANALISIS KEPUASAN PENGGUNA APLIKASI AUTOMATIC METER READING (AMR) MENGGUNAKAN METODE UTAUT - Anggi Fitra; Denny Kurniadi (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
This study aims to reveal the level of trust in the use of the AMR (Automatic Meter Reading) application implemented at PLN. The facts of satisfaction include performance expectancy, effort expectancy, social influence, facilitating conditions, and attitude. The research method used is descriptive research through the use of the UTAUT model. The purpose of this research is to determine the level of satisfaction in using AMR applications using the UTAUT method. The results of the study found that (1) the variable performance expectancy contributed 8.1%, obtained from the percentage contribution of the performance expectancy variable to the Behavioral Intention to use system in the acceptance and use of the Automatic Meter Reading (AMR) system (2) the effort expectancy variable contributed 13, 6%, obtained from the percentage contribution of the effort expectancy variable to use the system in the acceptance and use of the Automatic Meter Reading (AMR) system (3) the social influence variable contributes 21.16%, obtained from the percentage contribution of the social influence variable to the Behavioral Intention to use system In the acceptance and use of the Automatic Meter Reading (AMR) system (4) the facilitating conditions variable contributes 23.52%, the results are the percentage of contribution of the facilitating conditions variable to the intention of use behavior towards the Behavioral Intention to use system (BIUS) and (5) the variable Attitude contributed 10.43%, obtained didap from the percentage contribution of the Attitude variable to the Behavioral Intention to use system in the acceptance and use of the Automatic Meter Reading (AMR) system.